2012
DOI: 10.1088/0964-1726/21/4/045018
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermomechanical functionality of a laser processed hybrid NiTi–NiTiCu shape memory alloy

Abstract: The exciting thermomechanical behavior of NiTi shape memory alloys (SMAs) has sparked significant research effort seeking to exploit their exotic properties. The performance capabilities of conventional NiTi offerings are limited, however, by current fabrication technologies. In this study, a high power density laser source was implemented to locally alloy Cu into a conventional NiTi material. The effects of laser processing created a localized NiTiCu ternary material domain which possessed a set of unique the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Synergistic vaporization and mixing of additional alloying elements can also be achieved using laser processing on more complex alloy systems. [45] MMMs have the potential to greatly enable the engineering of complex SMA devices. SMA functionality has been immensely improved where concepts such as, but not limited to, dynamic actuation via passive atmospheric control, selfbiasing monolithic actuators, and local tuning of functional properties are now feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic vaporization and mixing of additional alloying elements can also be achieved using laser processing on more complex alloy systems. [45] MMMs have the potential to greatly enable the engineering of complex SMA devices. SMA functionality has been immensely improved where concepts such as, but not limited to, dynamic actuation via passive atmospheric control, selfbiasing monolithic actuators, and local tuning of functional properties are now feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to precisely and rapidly tune the local material properties, opposed to traditional inaccurate and slow bulk processes, make lasers excellent candidates for SMA processing. For example technologies such as, laser induced vaporization [14][15][16][17][18][19] and local laser annealing [20], have shown great potential to revolutionize the fabrication and design of devices. In these novel laser technologies, rapid local changes in microstructure and/or chemical composition have been shown to effectively fine tune both the pseudoelastic and shape memory properties of NiTi SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have shown that exposure to high-density laser energy can alter thermomechanical behavior in NiTi by shifting phase transformation onset temperatures within the processing region (Daly et al, 2011(Daly et al, , 2012Khan and Zhou, 2010a;Pequegnat et al, 2011). This technique, referred to as multiple memory material (MMM) technology, can be used to locally tune the thermomechanical response of conventional NiTi SMAs (Khan andZhou, 2010b, 2011).…”
Section: Introductionmentioning
confidence: 99%